2008
DOI: 10.1128/jb.00259-08
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Metabolism and PrfA Activity inListeria monocytogenes

Abstract: Listeria monocytogenes is able to efficiently utilize glycerol as a carbon source. In a defined minimal medium, the growth rate (during balanced growth) in the presence of glycerol is similar to that in the presence of glucose or cellobiose. Comparative transcriptome analyses of L. monocytogenes showed high-level transcriptional upregulation of the genes known to be involved in glycerol uptake and metabolism (glpFK and glpD) in the presence of glycerol (compared to that in the presence of glucose and/or cellob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
115
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 55 publications
6
115
0
Order By: Relevance
“…PrfA activity is much higher in the presence of non-PTS carbon substrates such as glycerol (Joseph et al, 2008;Mertins et al, 2007). High PrfA activity is also observed in L. monocytogenes replicating inside mammalian host cells (Renzoni et al, 1999), where non-PTS carbon sources are used (Eylert et al, 2008;R.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…PrfA activity is much higher in the presence of non-PTS carbon substrates such as glycerol (Joseph et al, 2008;Mertins et al, 2007). High PrfA activity is also observed in L. monocytogenes replicating inside mammalian host cells (Renzoni et al, 1999), where non-PTS carbon sources are used (Eylert et al, 2008;R.…”
Section: Introductionmentioning
confidence: 76%
“…Our recent data (Joseph et al, 2008;Mertins et al, 2007) rather suggest that the phosphorylation state of the PTS permeases required for the uptake of the above-mentioned carbohydrates seems to correlate with the PrfA activity. Based on these data we proposed a model (Joseph et al, 2008) which assumes that the unphosphorylated PTS permease (which is the principal state during active sugar transport, as the phosphate group is transferred to the sugar) may inhibit PrfA activity, possibly by binding directly to PrfA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…lmo0398 and lmo0399 were previously proposed to play a role in s B -dependent regulation of carbohydrate metabolism during low nutrient energy stress conditions encountered during stationary phase (Chaturongakul et al, 2008). Interestingly, the gene encoding Lmo1539, a Group D protein involved in the uptake of glycerol, which L. monocytogenes can utilize as a carbon source for growth (Joseph et al, 2008;Premaratne et al, 1991), was found to be negatively regulated by s B in the 10403S microarray analyses conducted by Raengpradub et al (2008) and Oliver et al (2010) (FC50.2 and 0.5, respectively; P,0.01 in both studies), but was not found to be significantly differentially expressed in the microarray comparison of a prfA* and prfA*DsigB strain (Ollinger et al, 2009). However, lmo1539 was found to be upregulated during intracellular replication (Chatterjee et al, 2006) and in a s B -dependent manner in the intestine (Toledo-Arana et al, 2009) using L. monocytogenes strain EGD-e, during stationary phase stress using L. monocytogenes strains FSL J1-194, FSL J2-071 and FSL J1-208 (Oliver et al, 2010), and showed evidence for positive regulation by s B using L. monocytogenes strain 10403S when FPSS (fluorophenylstyrene sulfonamide) was used to inhibit s B activation (Palmer et al, 2011).…”
mentioning
confidence: 99%